Macroeconomic Risk Factor in Fuzzy Present Value of Highway Development - Salihah Shaffie, Siti; Hafizah Jaaman, Saiful; Mohamad, Daud (International Journal of Engineering and Technology, 2018)
Highway developments are the backbone for the society and economic growth. It is part of the capital investment in infrastructure developments that require high spending, long term commitment and prognosticated with numbers of risks. This is because the investment is associated with uncertainty and vagueness due to long term duration of construction and operation of the project. Hence, the valuation of the investment requires accommodated model to present more accurate estimation of the project. This study proposed to evaluate fuzzy present value of a highway project with anticipated risk assessment in its valuation using fuzzy present value. The risk assessment is part of the estimation of fuzzy cash flow to represent better present value of the project. The results show an estimated value comprise with risk assessment of macroeconomic factor to portray better estimation that can assist decision maker to make decision towards the project. Â Â